New strategy of closed suction drainage after primary total hip arthroplasty - Gun-Woo Lee; Kyung-Soon Park; Do-Youn Kim; Young-Rok Shin; Taek-Rim Yoon (Acta Orthopaedica et Traumatologica Turcica)
Objective: The purpose of this study was to evaluate the effect of late applied negative pressure on postoperative drain output after primary total hip arthroplasty (THA). Patients and methods: 100 patients (100 hips) were treated by closed suction drainage applying negative pressure immediately after THA (group I). The remaining 100 patients (100 hips) were treated by the same drainage system, but the negative pressure was not applied in the first 24 h after THA and then negative pressure was applied (group II). Results: The mean total drain output was different between the two groups (group I: 597 ± 200.1 mL, group II: 403 ± 204.1 mL; p < 0.05). Reported drain output from immediate postoperative to postoperative day one was 369 ± 125.5 ml in group I and 221 ± 141.3 ml in group II (p < 0.05). The change of hemoglobin from immediate postoperative to 24 h after THA was lower in group II (group I: 1.5 ± 0.62 g/dL, group II: 1.1 ± 0.73 g/dL; p = 0.004). The mean unit number of blood transfusions was 1.0 (range, 0.0–5.0) in group I and 0.3 (range, 0.0–2.0) in group II (p < 0.05). There was no difference in Harris hip score between the two groups at postoperative 1 year or last follow-up (p = 0.073). Conclusion: The minor change in drain system management can reduce postoperative blood loss after primary THA and the need for transfusion.Level of evidence: Level III, Therapeutic study Keywords: Closed suction, Drainage, Total hip arthroplasty, Blood loss, Transfusion